Study on the microstructural evolution of different component alloys consisting of B2-NiSc intermetallics - Yuan, Zhipeng (Array, 2019)
Ni-50%Sc and Ni-51%Sc alloy were prepared with a vacuum arc smelting and water cooled copper mold suction-casting machine. The results showed that the two component alloys consisted of the primary phase B2-NiSc and lamellar (Ni2Sc+NiSc)eutectic due to the loss of Sc during melting. Two groups of alloys underwent (970 ℃, 72 h) homogenization heat treatment, and spherical or plate shape Ni2Sc particles were dispersed on the B2-NiSc matrix. With the increase of Sc content from 50% to 51%, the amount of the second phase in the alloy decreases, the microstructure becomes uniform, and the grain gradually changes from long bar to a spherical particle. According to the Jackson boundary theory, the Jackson factor α of B2-NiSc =0.5 <2, so the interface is rough, which explains that the growth pattern of the B2-NiSc phase is a non-faceted growth. It is consistent with the dendritic growth pattern of the B2-NiSc phase, which is observed from the experiment. After a long heat treatment, the number of vacancies decreases and the microstructure became uniform. The loss rate of Sc in rapidly quenched solidification was higher than that after the heat treatment.